Flow‐through immobilized enzyme reactors based on monoliths: I. Preparation of heterogeneous biocatalysts. Issue 1 (6th January 2013) - Vlakh, Evgenia G.; Tennikova, Tatiana B.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The application of monoliths for realization of solid‐phase biocatalytic processes was dramatically extended since the beginning of new century. Different enzyme immobilization techniques regarding these modern stationary phases have been developed, adapted, and optimized within last decade. The choice of enzyme immobilization method depends on material nature and monolith manufacturing. The present review collected, analyzed, and discussed the accessible published data on existing approaches and specialties of preparation of flow‐through enzyme reactors based on monoliths.